(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
Idioms are considered the main tools in the English language.There are also alternative versions of some idioms with Uzbek expressions.This article analyzes the similarities and differences of phraseological units in English and Uzbek. In addition, figurative expressions in both languages are studied comparatively from semantic, stylistic, and cultural points of view. In addition, the connection of ideoms with the culture, values, and national thinking of the people is highlighted. Some idioms in English are shown with corresponding variants in Uzbek based on examples, and the problems in the translation process are fully analyzed.